Trichloroethylene exposure alters dimethylated histone three lysine four in protein kinase A signaling pathway chromatin of rat sperm. Issue 5 (20th August 2019) - Stermer, Angela R; Wilson, Shelby K; Klein, David; Hall, Susan J; Boekelheide, Kim
Abstract: Histone three lysine four dimethylation (H3k4me2) in sperm is conserved across species and is linked to transgenerational epigenetic inheritance. To test whether H3K4me2 is a target for transgenerational inheritance of toxicity, a daily gavage bolus exposure of trichloroethylene (TCE) (1000 mg/kg/day) was given to rats for 14 weeks, then epididymal sperm were isolated and native chromatin immunoprecipitation followed by next generation sequencing (ChIP-seq) of H3K4me2 was performed. Differential region analysis determined there were 2608 significantly differential H3K4me2 regions after TCE exposure, 477 were significantly increased and 2131 were significantly decreased. Z-score enrichment of differential regions determined there were significantly decreased H3k4me2 in the coding and regulatory regions of genes in the PKA signaling pathway. These changes account for TCE induced spermatozoal toxicity and show H3K4me2 is a target for paternal inheritance of toxicity.